The Influence of Three Stage Fishbowl Decision Learning Method On Mathematical Learning Ability - Tua Haloman; Asrar Aspia Manurung (Indonesian Journal of Education and Mathematical Science, 2019)
This study aims to determine the effect of the application of the Three Stage Fishbowl Decision learning method to the ability to learn mathematics in students of SMK Muhammadiyah 9 Medan and how significant the Three Stage Fishbowl Decision learning method affects the mathematics learning ability of students of SMK Muhammadiyah 9 MedanT.P 2016/2017 . The research instrument used was a test in the form of awa l test (pretest) and final test (post-test) consisting of 5 items each of the initial test (pretest) and 5 items of the final test (post-test). The validity test results of 15 item items obtained were 11 valid item items and 4 invalid item items. As the population of this study all students of class XI of SMK Muhammadiyah 9 Medan totaled 93 students, so the sample in this study was class XI TKR which numbered 68 students. The reliability test results of 15 valid obtained that 11 questions were reliable. After raining data the mathematical understanding ability was found to be tcount> ttable, thitung (5.34)> ttable (1.99656). Then Hα is accepted and H0 is rejected. So it can be concluded from the hypothesis test that students' mathematics learning ability in the experimental class is better than the control class. This means that there is an influence between the Three Stage Fishbowl Decision learning method on the ability to learn mathematics in students of SMK Muhammadiyah 9 Medan T.P 2016/2017. The magnitude of the influence of Three Stage Fishbowl Decision learning methods on the ability to learn mathematics cubes and blocks in class XI students of SMK Muhammadiyah 9 Medan T.P 2016/2017 is 2.89%